USER SATISFACTION ANALYSIS OF DANA APPLICATION USING END USER COMPUTING SATISFACTION METHOD - Aritonang, Sudarsono; Prabowo, Dedy Agung; Ramdani, Cepi (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The XYZ e-wallet application provides convenience in non-cash transactions with various features. Even though it allows for comfort in commerce, there are deficiencies in the XYZ e-wallet application that make users feel uncomfortable and dissatisfied. Weaknesses in the XYZ e-wallet application, namely there are problems updating the XYZ e-wallet to Premium, it is difficult to make payments to merchants who work with the XYZ e-wallet application, and there are problems with e-wallet application services on the service menu reporting problems response the customer service of the XYZ e-wallet application is old and ineffective. The results of the pre-research questionnaire on 59 answers found that 54.2% of respondents needed help making transactions. As many as 61% of users are dissatisfied with the services provided by the XYZ e-wallet application. This research analyzed user satisfaction with the XYZ e-wallet application using the EUCS method. This method measures five variables: Content, Accuracy, Format, Ease of Use, and Timelines. Each variable is measured with four questions. The results showed that the variables Content, Format, and Ease of Use were satisfied with Very Satisfied criteria, while the Accuracy and Timeliness variables had Satisfied criteria. The smallest calculated value is in the Accuracy and Timeliness variables which discuss the accuracy of errors when making transfers, upgrading the XYZ e-wallet account to Premium, and timeliness in handling problem reports. This research analyzed user satisfaction with the XYZ e-wallet application using the EUCS method. This method measures five variables: Content, Accuracy, Format, Ease of Use, and Timelines. Each variable is measured with four questions. The results showed that the variables Content, Format, and Ease of Use were satisfied with Very Satisfied criteria, while the Accuracy and Timeliness variables had Satisfied criteria. The smallest calculated value is in the Accuracy and Timeliness variables which discuss the accuracy of errors when making transfers, upgrading the XYZ e-wallet account to Premium, and timeliness in handling problem reports. This research analyzed user satisfaction with the XYZ e-wallet application using the EUCS method. This method measures five variables: Content, Accuracy, Format, Ease of Use, and Timelines. Each variable is measured with four questions. The results showed that the variables Content, Format, and Ease of Use were satisfied with Very Satisfied criteria, while the Accuracy and Timeliness variables had Satisfied criteria. The smallest calculated value is in the Accuracy and Timeliness variables which discuss the accuracy of errors when making transfers, upgrading the XYZ e-wallet account to Premium, and timeliness in handling problem reports. Each variable is measured with four questions. The results showed that the variables Content, Format, and Ease of Use were satisfied with Very Satisfied criteria, while the Accuracy and Timeliness variables had Satisfied criteria. The smallest calculated value is in the Accuracy and Timeliness variables which discuss the accuracy of errors when making transfers, upgrading the XYZ e-wallet account to Premium, and timeliness in handling problem reports. Each variable is measured with four questions. The results showed that the variables Content, Format, and Ease of Use were satisfied with Very Satisfied criteria, while the Accuracy and Timeliness variables had Satisfied criteria. The smallest calculated value is in the Accuracy and Timeliness variables which discuss the accuracy of errors when making transfers, upgrading the XYZ e-wallet account to Premium, and timeliness in handling problem reports